Plan de negocio para la producción y exportación de mermelada de uvilla hacia Hamburgo-Alemania - Padilla Sandoval, Alan Israel (2019)
This business plan is based on the creation of a company for the production and export of marmalade based on uvilla to the market of Hamburg-Germany, focused on making jams that do not contain preservatives, with uvillas of the best quality, guaranteeing a 100 percent organic product, for which it is necessary to understand certain components that guarantee the viability of the project, taking into account variable research. The company is totally focused on making known the great benefits of producing fruits in the Ecuadorian soil, since Ecuador is considered one of the richest countries in flora and fauna, where all kinds of fruits are very well given, apart from have very sweet fruits, compared to fruits from other countries, which gives us a comparative advantage with the rest of the world. The gathering of information revealed that there is a high number of competitors, mostly local ones, which satisfy the Hamburg market, but likewise the investigation resulted in customers starting to look for exotic, sweet and organic products, where they have not yet This niche has been exploited. The brand with which the marmalade will be identified will be süße marmelade, which means in German sweet jam, this name conveys confidence, and above all the certainty that it is a jam rich in flavor and texture. In terms of finance, the company will have profitability, and liquidity, which will be useful for future projects of asset acquisition or expansion.